2014
DOI: 10.1097/mph.0000000000000033
|View full text |Cite
|
Sign up to set email alerts
|

Homozygous Antithrombin Deficiency in Adolescents Presenting With Lower Extremity Thrombosis and Renal Complications

Abstract: We present 2 cases of lower extremity deep venous thrombosis in 2 gypsy adolescents from related families. The patients had low antithrombin activity levels and inherited homozygous antithrombin deficiency was confirmed by molecular analysis (Leu131Phe mutation). One patient had a history of nephrectomy at the age of 9 due to nonfunctioning kidney and 2 siblings died at 4 months of age. His mother had 3 fetal losses in the third trimester. The other propositus had an elder sister who suffered from postpartum d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…However, few published cases of patients with homozygous mutations in the heparin-binding site (HBS) have suggested that homozygosity results in an earlier presentation of thrombotic disease 12. Moreover, the replacement of threonine-85 (Thr-85) methionine (known as antithrombin-Wibble) results in a mild adult-onset thrombotic disease, whereas replacement of the same Thr-85 by lysine (known as antithrombin-Wobble) results in early childhood onset of thrombosis 12…”
Section: Discussionmentioning
confidence: 99%
“…However, few published cases of patients with homozygous mutations in the heparin-binding site (HBS) have suggested that homozygosity results in an earlier presentation of thrombotic disease 12. Moreover, the replacement of threonine-85 (Thr-85) methionine (known as antithrombin-Wibble) results in a mild adult-onset thrombotic disease, whereas replacement of the same Thr-85 by lysine (known as antithrombin-Wobble) results in early childhood onset of thrombosis 12…”
Section: Discussionmentioning
confidence: 99%
“…In heterozygous form, VTE can manifest in early adolescence or younger adulthood [41], and patients with inherited thrombophilia remain at a heightened risk of VTE throughout their lifetime [4,42]. Based on antithrombin functional activity and quantity, inherited antithrombin deficiency is categorized into two types: Inherited type I antithrombin deficiency and inherited type II antithrombin deficiency [43,44].…”
Section: Hereditary/congenital Antithrombin Deficiencymentioning
confidence: 99%
“…It was first described in 1965 in a Scandinavian family [1]. Inherited AT de ciencies are uncommon, with prevalence in the general healthy population being 1 in 5000 and in patients with a history of thrombosis 1 in 500 [2,3]. Most of patients have quantitative type I deficiency associated with proportional decrease of protein activity and antigen levels while type II is a qualitative deficiency leading to discrepancy between AT activity and antigen levels and causing dysfunction of the protein.…”
Section: Introductionmentioning
confidence: 99%